A Few Good Companies: Rethinking Firms’ Responsibilities Toward Common Pool Resources - Gabaldon, Patricia (Journal of business ethics, 2015)
While a significant body of literature has highlighted the moral obligations of companies regarding the sustainable use of common pool resources, business activities that contribute to the sustenance of common pool resources remain embryonic. Studies in this area have largely focused on environmental stimuli rather than on the complex motivational structures that drive or hinder businesses’ contributions to common pool resources. We explore the different motives and behaviors of businesses and their contributions to common pool resources, and propose four roles by which companies’ motives and behaviors toward common pool resources can be categorized—namely, free riders, followers, believers, and altruists. We shift the focus from moral reasoning to Platt’s (Am Psychol 28(8):641–651, 1973) notion of social trapping and his “ways out” as Platt’s “ways out” include propositions that address not only environmental stimuli but also companies’ motives. Both types of propositions are important for businesses to be able to respond rapidly to the scarcity of certain common pool resources and to use and maintain common pool resources in a sustainable way. Based on our categorization and Platt’s typology of social traps and “ways out,” we propose a theoretical framework by which companies and other stakeholders are provided with a differentiating perspective that allows for propositions addressing the complex nature of motivational structures and common pool resources. Our framework helps business leaders, institutions, and policy makers decide on actions that can contribute to the sustainability of common pool resources and that differ from actions that solely serve organizational self-interests.